Lymphatic filariasis in India - Kambam, S. R. (Запорізький державний медичний університет, 2019)
Introduction. Human Lymphatic filariasis has become one of the most significant public health problem in the tropics. More than 1.4 billion people in 73 countries are living in areas where lymphatic filariasis is transmitted and an estimated 80 to 120 million people at risk of being infected. Ait. To stady the distribution and pathological effects of Filaria in India. Methods and materials. Internet, statistical data, literature authored by Dr. Anantha Narayan Text-book of parasitology.
Keywords: тези доповідей